Interplay of Acid-Base Ratio and Recycling on the Pretreatment Performance of the Protic Ionic Liquid Monoethanolammonium Acetate - Nakasu, Pedro Y. S.; Clarke, Coby J.; Rabelo, Sarita C. [UNESP]; Costa, Aline C.; Brandt-Talbot, Agnieszka; Hallett, Jason P. (American Chemical Society (ACS), 2020)
The use of protic ammonium ionic liquids (PILs) in the pretreatment of lignocellulosic biomass is a promising alternative to using expensive aprotic ionic liquids such as 1-ethyl-3-methylimidazolium acetate, [Emim][OAc]. In this work, the PIL monoethanolammonium acetate, [MEA][OAc], was used for the pretreatment of sugar cane bagasse. The study investigated changing the acid base ratio (ABR) from 0.1 to 10 and recycling of the solvent. We determined the lignin extraction, lignin recovery, solvent recovery, and enzymatic saccharification yield and compared the performance to that of the pure amine base, monoethanolamine. We found that lignin extraction and glucose release during enzymatic saccharification increased with base (amine) content, reaching up to 84% and 96%, respectively, after 72 h of saccharification for the 0.1 ABR. Up to 97% of the solvent was recovered for the 1.0 ABR. A higher acid content led to increased hemicellulose extraction into the liquid phase and reduced ionic liquid recovery. A partial conversion of the PIL into N-(hydroxyethyl) acetamide was observed after pretreatment, with up to 86% of conversion after the sixth use for the 1.0 ABR. A negative correlation (R2 = 0.96) was found between the acetamide content in the solvent and the saccharification yield. The drop in pretreatment performance was also correlated with a decrease in accumulated lignin recovery and the molecular weight of the isolated lignins. Acetamide formation was reduced when excess base was present. Recycling of the mixture with 0.5 ABR showed that the performance was unchanged (97% saccharification yield) after three uses, although 28% of the mixture was converted into the acetamide. The study shows that protic acetate ILs made from primary amines form an equilibrium with their amide and a low ABR is required in order to maintain high pretreatment efficiency when the PIL is reused.
Keywords: Acid base ratio; Pretreatment; Protic ionic liquid; Solvent recycling; Sugar cane bagasse